Mature T-Cell leukemias: Challenges in Diagnosis - El-Sharkawi, Dima; Attygalle, Ayoma; Dearden, Claire (Frontiers in Oncology, 2022)
T cell clones can frequently be identified in peripheral blood. It can be difficult to appreciate whether these are benign and transient or whether they signify a clonal disorder. We review factors that aid in understanding the relevance of T-cell clones. Conversely, obviously pathological T- cell clones can be detected in blood, but there is uncertainty in how to categorise this clonal t cell population, we adopt a multidisciplinary review of the clinical features, diagnostic material, and radiology before making the diagnosis. In this review we shall discuss some of these challenges faced when diagnosing mature T- cell leukaemias.